KADAR KOLESTEROL DAGING DAN KUALITAS KARKAS AYAM PEDAGING DENGAN PENGGUNAAN TEPUNG BAWANG PUTIH DALAM RANSUM - Marfuah, Nuun (FAPETKAN UNTAD, 2016)
Chicken meat is an animal product for bussines. The meat is consumed nearly everyday by human being. Uncontrolled use of antibiotics in animal feed produces a negative impact on both animal and human being, who consume animal product. As a traditional herbal, garlic has an active substance called allicin. This active substance can be used to improve performance and carcass quality of broilers. An experiment was conducted to study effect of garlic meal in the diet on cholesterol and carcass quality of broilers. A total of 100 day old chicks has used. A completely randomized design was adapted with 5 treatment and 4 raplicate cages of birds each. Differences every treatment were tested with Duncanâ€™s multiple range test. Experimental diets used were : control diet (R0), 1.5% garlic meal (R1), 3% garlic meal (R2), 4.5% garlic meal (R3) and 6% garlic meal (R4). Feed and water were offered ad libitum, birds were kept for 42 days for performance and carcass quality data. Three birds from each cage were slangheered for measuring cholesterol. The result showed that treatment gave a significant effect (P<0.05) on meat cholesterol levels. However, feed intake, carcass percentage, carcass parts and abdominal fat was not significantly (P>0.05) affected by treatment R3 with 4.5% garlic meal produced the best result. In conclusion, the result of this study indicated that the use of garlic meal in the diet result in good cholesterol and carcass quality.Â Key words : Garlic, Cholesterol, Carcass Quality